Al-Quran dan Keautentikannya; Kajian tentang Rasm Al-Qur’an dalam Mushaf Uthmani - Herfin Fahri (LPPM Institut Agama Islam Al-Hikmah Tuban, 2020)
Al-Quran is one of the names of a book that was revealed to the Prophet Muhammad, through the angel Gabriel written in the Manuscripts, and narrated mutmutually. It is said that one of the names means there are other names that must be investigated, and it is also necessary to find the root word of the Qur’an in order to have knowledge about the Qur’an as a holy book. Because the Koran is the Kalamullah revealed to the Prophet Muhammad through the Angel Gabriel, it is also necessary to examine how the Qur’an can finally be written and standardized as the Koran can be witnessed today. Rasm Uthmani is a form of writing or procedures for writing the Koran which is blessed or which has been established at the time of the caliph ‘Uthmān bin‘ Affān r.a. and the term rasm 'Uthmani was born at the same time as the birth of the Ottoman Manuscripts, the rasm has been a custom inherited by Muslims since the era of' Uthmān ra, and the maintenance of rasm 'Uthmani is a strong guarantee for safeguarding the Qur'an from changing and changing its letters, and if allowed to write according to the term imla'i every time it will cause changes in the writing of the Koran from time to time, even the rules of the Imla 'itself vary intendencies at the same time, and also vary in a few words between one country and another. On the other hand there are some opinions questioning the authenticity of the al-Quran manuscript, so that the term scripto plene (perfect manuscript) or official corpus such as al-Quran is formed today, was formed in the 3 H / 9 M, and other opinion is the Qur’an in the form of scriptio defectiva ( rudimentary manuscript). Keyword: rasm al-Quran, mushaf ‘uthmani,